How to Solve Water Shortage Problem By Means of Renewable Power Generation? - Nazarova, Yulia Alexandrovna; Sopilko, Natalya Yuryevna; Kovaleva, Ekaterina Alexandrovna; Kulakov, Andrey Valentinovich; Orlova, Anzhelika Feliksovna; Gavlovskaya, Galina Valentinovna (International Journal of Energy Economics and Policy, 2018)
The article is devoted to one of the global humanity problems – increasing drinking water shortage. The authors analyzed statistic data of Russian federal districts and emphasized the most problem regions. The authors proposed an innovative technology of renewable power sources as a way of water supply increasing; they analyzed perspectives of renewable power engineering in Russia according to solution of a fresh water shortage problem. Development of renewable power engineering was considered as one of the ways of water supply increasing. On the basis of the research the authors formulated an economic-mathematical model. The model assessed a capacity of a water condensing combined wind driven electric plant (WDEP) under the various weather conditions – an average temperature and humidity of the air. According to the model a perspective water output under the conditions of Republic of Crimea was foreseen. The authors came to the conclusion that a combined WDEP could be used for water supply in the further-flung regions, for agriculture, production and fire extinguishment. Keywords: Renewable energy, wind driven electric plant, solar forced circulation system JEL Classifications: Q250, Q420. DOI: https://doi.org/10.32479/ijeep.7342